Pemikiran Politik Islam pada Masa Kolonialisme dan Pasca Kolonialisme - Putri Lestari Kusuma; Muhammad Arval; Marzuki Marzuki; Pausi Rahman (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This paper explores the dynamics of Islamic political thought during the colonial and post-colonial periods through the contributions of three prominent figures: Sayyid Jamaluddin al-Afghani, Muhammad Abduh, and Rashid Rida. These three pioneers of Islamic reform responded to the decline of the Muslim world and the dominance of Western imperialism by offering ideological, political, and social solutions. Al-Afghani emphasized the importance of Muslim unity through the idea of pan-Islamism and revolutionary resistance against despotic rule and foreign colonization. Muhammad Abduh advocated for the reform of Islamic thought through rational interpretation, rejection of blind imitation (taqlid), and the application of democratic principles and social justice. Rashid Rida, with a more systematic approach, developed the concept of the caliphate as the ideal political institution in Islam and stressed the importance of reforming the governance system based on the principles of Sharia and tawhid. Their ideas laid a crucial foundation for the development of modern Islamic political discourse and offered direction for the Muslim struggle to establish a just, independent socio-political order aligned with Islamic values in the post-colonial era.